2015
DOI: 10.1155/2015/843058
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cells Derived from Induced Pluripotent Stem Cells Support CD34posHematopoietic Stem Cell Propagation and Suppress Inflammatory Reaction

Abstract: Mesenchymal stem/stromal cells (MSCs) represent a promising cell source for research and therapeutic applications, but their restricted ex vivo propagation capabilities limit putative applications. Substantial self-renewing of stem cells can be achieved by reprogramming cells into induced pluripotent stem cells (iPSCs) that can be easily expanded as undifferentiated cells even in mass culture. Here, we investigated a differentiation protocol enabling the generation and selection of human iPSC-derived MSCs exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 56 publications
2
23
0
4
Order By: Relevance
“…Previously, we showed that iPSC-MSCs displayed a shorter doubling time than BM-MSCs and reached senescence at later passages than BM-MSCs [10]. To investigate the effects of Kindlin-2 on proliferation and survival in iPS-MSCs, we performed a BrdU incorporation assay (Figure 2(a)) that showed a significant increase after Kindlin-2 Flag transfection compared to the vector control.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we showed that iPSC-MSCs displayed a shorter doubling time than BM-MSCs and reached senescence at later passages than BM-MSCs [10]. To investigate the effects of Kindlin-2 on proliferation and survival in iPS-MSCs, we performed a BrdU incorporation assay (Figure 2(a)) that showed a significant increase after Kindlin-2 Flag transfection compared to the vector control.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were split weekly using collagenase IV (Thermo Fisher), and cells were plated on Matrigel-coated (Corning) plates. Differentiation/enrichment of iPSCs to MSCs was conducted as described [10]. In brief, human iPSC colonies grown on Matrigel were maintained with MSC induction media consisting of DMEM (low-glucose, Sigma-Aldrich, Darmstadt, Germany), 10% defined fetal bovine serum (FBS, Stem Cell Technologies, Vancouver, BC, Canada), 1% nonessential amino acids, 1% penicillin-streptomycin, and 2 ng/mL human recombinant bFGF for 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations